Polonistyka koreańska wczoraj i dziś - Byung-Kwon, Cheong (Postscriptum Polonistyczne, 2020)
The article presents the history of Polish Studies at the University of Foreign Languages in Seul. The author, who is the Head of Polish Department, discusses its foundation and development. He presents also the activity of the Department over past twenty years – shaping of the curricula and their present form, activity of the staff in the field of academic research and translations, and international cooperation. Polish department at Hankuk University of Foreign Studies was founded in 1987 and it initiated Polish Studies in Korea. Currently, about 130 people are studying there. Classes are held by 10 teachers and scholars, two people from Poland among them. Graduates of the Department are likely to obtain employment, due to the good economic relations between Poland and Korea.